2018
DOI: 10.1155/2018/4503871
|View full text |Cite
|
Sign up to set email alerts
|

Significant Changes in Plasma Alpha-Synuclein and Beta-Synuclein Levels in Male Children with Autism Spectrum Disorder

Abstract: Alpha-synuclein (α-synuclein) and beta-synuclein (β-synuclein) are presynaptic proteins playing important roles in neuronal plasticity and synaptic vesicle regulation. To evaluate the association of these two proteins and autism spectrum disorder (ASD), we investigated the plasma α-synuclein and β-synuclein levels in 39 male children with ASD (2 subgroups: 25 autism and 14 pervasive developmental disorder-not otherwise specified (PDD-NOS)) comparing with 29 sex- and age-matched controls by using enzyme-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…A study by Kadak et al [ 23 ] found a low serum level of a-syn in ASD children (mean values 33.01 ± 20.78 ng/ml) compared to controls (mean values 241.23 ± 290.5 ng/ml). Sriwimol and Limprasert [ 13 ] in another study done on 39 ASD male children, confirms the observation of significantly lower plasma a-syn-mono levels (mean values 10.82 ± 6.46 ng/ml) in the plasma of ASD children compared to healthy controls (mean values 29.47 ± 18.82 ng/ml). The present study on the saliva of 40 ASD children comprising both male and female subjects not only supports the results mentioned above but also establishes the importance and usability of “saliva” as an essential body secretion.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…A study by Kadak et al [ 23 ] found a low serum level of a-syn in ASD children (mean values 33.01 ± 20.78 ng/ml) compared to controls (mean values 241.23 ± 290.5 ng/ml). Sriwimol and Limprasert [ 13 ] in another study done on 39 ASD male children, confirms the observation of significantly lower plasma a-syn-mono levels (mean values 10.82 ± 6.46 ng/ml) in the plasma of ASD children compared to healthy controls (mean values 29.47 ± 18.82 ng/ml). The present study on the saliva of 40 ASD children comprising both male and female subjects not only supports the results mentioned above but also establishes the importance and usability of “saliva” as an essential body secretion.…”
Section: Discussionsupporting
confidence: 58%
“…In degenerative diseases like PD a-syn-mono becomes abnormally aggregated into a-synuclein oligomers (a-syn-oligo), which is then converted into amyloid fibrils an ultimate precursor of Lewy bodies [ 15 ]. This fact establishes that a-syn-oligo is the main neurotoxic form of a-syn [ 13 ]. A-syn-oligo is present in CSF, plasma, peripheral nerve fibers, gut, skin, and salivary glands and saliva of PD patients [ 16 ].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In recent studies of children with autism spectrum disorder [39] and with attention-deficit/hyperactivity disorder, serum α-synuclein levels are reported to be low or no changes compared to controls [40]. Therefore serum α-synuclein levels may suggest neurodegenerative process related with neuroinflammation in children.…”
Section: Discussionmentioning
confidence: 99%
“…A study in 39 children with ASD (age 2-8 years) without known karyotypic abnormalities showed a significant 3-fold decrease in α-syn plasma levels versus controls, which links one of the key proteins in PD pathogenesis to ASD. In this study, beta-synuclein (β-syn) levels were also found to be significantly higher in ASD children compared control group, postulating a compensatory effect of β-syn [68]. This overlapping clinical phenomenology of motor and non-motor symptoms and molecular link between ASD and PD point towards potentially converging disease mechanisms and imbalances of dopamine signaling in the basal ganglia.…”
Section: Overlapping Clinical Motor and Behavioral Phenomenology Betwmentioning
confidence: 59%